Вклад интерференцииоператоров O7–O8 для распада B → Xsγγ - Асатрян, Г. Г.; Асатрян, Г. М.; Тумасян, С. А.
Редкие распады B-мезонов позволяют исследовать физику вне Стандартной Модели. Для процесса B→ Xs γγ потенциальная новая физика должна быть ясно видна не только для ширины распада, но и в дифференциальных распределениях по параметрам (s1 , s2 ) , которые определены как si=( pb - qi )2 / mb2 , (i = 1, 2), где pb , q1 , q2 — импульсы b-кварка и двух фотонов. В работе рассчитан вклад порядка αs интерференции операторов O7-O8 . Мы также учитываем зависимость результатов от массы s-кварка при изменении ms в диапазоне 400–600 МэВ. Вклад интерференции операторов O7 -O8 в ширину распада B → Xs γγ в рассматриваемой нами области фазового пространства составляет 2–3%. Rare decays of B-mesons allow investigations of physics outside of the SM. ForB→ Xs γγ potential new physics should be clearly visible not only for the width of the decay, but also in the differential distributions with respect to the parameters (s1 , s2 ) , defined assi=( pb - qi )2 / mb2 , (i = 1, 2), where pb , q1 , q2 are the momenta of the b-quark and the two photons. In the paper the contribution of order αs of the interference of the operators O7 -O8 was calculated. We also consider the dependency of the results from the mass of the s-quark by changing ms in the range 400–600 MeV. The contribution of the interference of the operators O7 -O8 in the width of the decay B →Xs γγ in the regions of the phase space considered by us is equal to 2–3%.
Keywords: Элементарные частицы